Modeling and simulation of creep response of sorghum stems: Towards an understanding of stem geometrical and material variations. (May 2022) - Zargar, Omid; Pharr, Matt; Muliana, Anastasia
Abstract : Sorghum [ Sorghum bicolor (L.) ] is a tropical grass that often suffers from structural failure (lodging) when subjected to wind, rain, and hail. During lodging, excessive lateral deflection occurs, which inherently correlates with the biomechanical properties of the stem. As such, a fundamental understanding of sorghum's biomechanical behavior is required to mitigate its propensity for lodging. Herein, we perform creep tests to characterize the mechanical behavior of Della genotype sorghum stems and their constituents, i.e., their rind and pith. This study also examines the influence of various testing geometries and boundary conditions on mechanical property characterization. We determine that small geometric irregularities typical of sorghum stems (e.g., from straight circular cylinders) do not affect their mechanical response in an overall engineering strain sense. However, these typical geometric irregularities do lead to nonuniform (localized) stresses and strains, thereby influencing the quantification of certain properties during mechanical testing. We also implement a viscoelastic constitutive model to describe the creep responses of the individual constituents (rind and pith), as to predict the overall biomechanical response of the stems. We find that even though the rind carries most of the load in the stem and itself does not show a significant time-dependent response, an overall time-dependent response of the stem still occurs, arising from viscoelastic effects in the pith.